Evaluating the psychometric properties of the Italian version of Benign Envy and Malicious Envy Scale among Italian workers - Paolo Soraci; Nadia Bevan; Renato Pisanti; Rocco Servidio; Mark D. Griffiths (Cogent Psychology)
The present study analyzed the psychometric properties of the Italian adaptation of the Benign Envy and Malicious Envy Scale (BEMES) in the workplace context. The scale’s construct, convergent, and discriminant validity were examined and compared with related constructs such as social comparison, life satisfaction, mental well-being, and psychological distress. A convenience sample of 507 Italian workers (M age = 35.15 years [SD = ±12.31]; 82.38% female) successfully completed an online survey. Confirmatory factor analyses showed the bi-factor structure of the BEMES did not provide a good fit to the data. Consequently, two items with low loadings were removed from their respective hypothesized latent factors. The scale’s reliability was satisfactory, demonstrating good internal consistency (Cronbach’s α = 0.74–0.80; McDonald’s ω = 0.75–0.80). The scale’s validity was supported by associations with related constructs: benign envy had significant positive associations with increased social comparison, higher life satisfaction, and better mental well-being, while having negative associations with anxiety, stress, and depression. Conversely, malicious envy had positive associations with anxiety, stress, depression, and increased social comparison, while having negative associations with higher life satisfaction and better mental well-being. Findings contribute to a better understanding of envy in occupational contexts.